Pharmacotherapy of Sepsis. Issue 2 (April 2015) - Pavlik, David J.; Simpson, Robert W.; Horn, Edward T.; King, Lauren; Finoli, Lauren
<x xml:space="preserve">Abstract</x> Treatment of sepsis involves prompt recognition and treatment to optimize outcome. Several medication considerations are pertinent to patients with sepsis, severe sepsis, and septic shock. Medications play a crucial role in providing resuscitation, hemodynamic support, resolution of infection, and reduction of complications of the disease. Over the past 20 years, significant focus has been devoted to the pharmacologic treatment of septic shock, resulting in significant advances and controversies. Ongoing research will continue to focus on this disease process and will continue to shape treatment in the future. The use of medication therapies directed at treatment of sepsis will be reviewed in this article.